Acidic Urine Is Associated With Poor Prognosis of Upper Tract Urothelial Carcinoma - Han, Jang Hee; Jeong, Seung-hwan; Yuk, Hyeong Dong; Jeong, Chang Wook; Kwak, Cheol; Ku, Ja Hyeon (Frontiers in Oncology, 2022)
Purpose: To assess the prognostic role of acidic urine (low urine pH) in upper tract urothelial cancer (UTUC). Materials and Methods: We reviewed patients enrolled in Seoul National University Prospectively Enrolled Registry for Urothelial Cancer-Upper Tract Urothelial Cancer (SUPER-UC-UTUC) who underwent surgical resection from March 2016 to December 2020 in Seoul National University Hospital (SNUH). Patients with non-urothelial cancer or those who are in condition at end-stage renal disease were excluded. Acidic urine was defined as urine pH ≤ 5.5. Results: A total of 293 patients with a mean age of 70.7±9.5 years were enrolled in this study. Pre-operative laboratory results showed a mean estimated glomerular filtration rate (eGFR) of 64.1±19.2 mL/min/1.73㎡ and a mean urine pH of 5.86 ± 0.66. Patients were subdivided into low (pH ≤ 5.5) and high (pH > 5.5) urine pH for comparison. As a result, all variables were comparable except for the T stage, which was significantly higher in the low urine pH group (p = 0.017). Cox regression analysis was preformed to assess the clinical impact of acidic urine on patient survival. Multivariate Cox regression analysis revealed that tumor multifocality (HR 2.07, p = 0.015), higher T stage (HR 1.54, p = 0.036), lymphovascular invasion (HR 1.69, p = 0.033), eGFR < 60 mL/min per 1.73 m2 (HR 1.56, p = 0.017), and acidic urine (HR 1.63, p < 0.01) independently decreased disease-free survival (DFS), while multifocality (HR 9.50, p < 0.01), higher T stage (HR 9.51, p = 0.001) and acidic urine (HR 10.36, p = 0.004) independently reduced the overall survival (OS). Conclusions: Acidic urine is independently associated with reduced DFS and OS in UTUC. Acidic urine contributing to acidic environment may promote acquisition of aggressive behavior of UTUC.